Investigating the effects of plant growth-promoting rhizobacteria isolates on germination and physiology status of durum wheat under salt stress - Khaled BOUFARES; Mostefa KOUADRIA; Mohamedi KARIMA; Yahia Naima MERDJET (Acta Agriculturae Slovenica)
The aim of this work is to evaluate the seedling growth and physiology status of wheat seeds inoculated with a suspension of eight plant growth-promoting rhizobacteria (PGPR) isolates. For this purpose, rhizobacteria strains were isolated from the roots of native plants growing in the Algerian steppe, then evaluated for their plant growth promotion (PGP) features, and finally applied on wheat seeds. The obtained results showed that the majority of the tested strains displayed pertinent PGP features. In in vitro experiments, results showed that salinity affected negatively seed germination and impaired plant growth while the inoculation with BC3, BC6 and BC7 strains induced a good germination rate and improved significantly the root length. In greenhouse experience, data demonstrated that non-inoculated plants accumulated a significant amount of osmoregulators (proline and glycine betaine), and recorded a decrease of their chlorophyll content, compared to inoculated plants, where the salinity tolerance of this latter has been much better with a high seedling growth as well as high chlorophyll and low osmolyte contents. The results may be a useful extension of our knowledge of the interaction between plant and PGPR, in view of their possible applications as a biofertilizer to improve plant growth in salinity-impacted regions.